IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN FIQH KELAS VIII DI MTS SALAFIYAH SYAFI’IYAH SEBLAK DIWEK JOMBANG - Mas’ud, Muhammad Ali; Masruroh, Laily (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2024)
Contextual learning is a learning approach that emphasizes the importance of relating learning material to situations and problems that exist in real life. Thus, students are expected to be able to connect and apply learning outcomes relevantly in everyday life. Based on the above, the authors have 2 research focuses, namely: 1) How is the application of contextual learning models in fiqh class VIII at MTs Salafiyah Syafi'iyah Seblak, Diwek Jombang. 2) What are the supporting and inhibiting factors in applying the contextual learning model to fiqh class VIII at MTs Salafiyah Syafi'iyah Seblak, Diwek, Jombang. The author specializes in choosing a qualitative research approach that is appropriate to the research subject being investigated.. The data was combined during observations, interviews and documentation involving madrasa heads, students and teachers. The research results in this thesis show that the application of contextual learning is very effective. Learning provides real examples of the material being taught, encouraging students to increase their understanding and knowledge in useful everyday life. Contextual learning strategies emphasize the full involvement of students in discovering and relating material to real life situations. Supporting factors include the existence of professional teachers, adequate facilities, and active behavior of students. Inhibiting factors include boredom, lack of motivation, and the last hour of class.